1990
DOI: 10.1111/j.1559-1816.1990.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Desires, Self‐Predictions, and Perceived Control in the Prediction of Training Session Attendance1

Abstract: Employee attendance at a training session was examined using the theory of reasoned action (Fishbein & Ajzen, 1975). In addition, based on Audi (1973a, b) and Warshaw and Davis (1985), a distinction was made between desires (I want) and behavioral self‐predictions (I will), and as in Ajzen (1985, 1987), the role of perceived control as a determinant of these desires, self‐predictions, and attendance behavior, per se, was investigated. The results indicated that the best predictors of attendance at the training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
127
2
3

Year Published

1992
1992
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(137 citation statements)
references
References 16 publications
5
127
2
3
Order By: Relevance
“…Previous studies have demonstrated close relationships between intention, desire, and expectation in predicting behaviour using the TPB model (Armitage & Conner, 2001;Fishbein & Stasson, 1990;Warshaw & Davis, 1985). Initial correlation analyses failed to show a significant relationship between intention and behaviour at any of the time points.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous studies have demonstrated close relationships between intention, desire, and expectation in predicting behaviour using the TPB model (Armitage & Conner, 2001;Fishbein & Stasson, 1990;Warshaw & Davis, 1985). Initial correlation analyses failed to show a significant relationship between intention and behaviour at any of the time points.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have demonstrated close relationships between intention, desire, and expectation in predicting behaviour using the TPB model (Armitage & Conner, 2001;Fishbein & Stasson, 1990;Warshaw & Davis, 1985). Expectations and desires have both been shown to be better than intentions at predicting behaviour (Fishbein & Stasson, 1990;Warshaw & Davis, 1985).…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, this model has validity both in the study of general consumer choice and the study specifically of food choice. The incorporation of perceived control has received some support in social psychological applications (for example, see Ajzen, 1988), and in studies of weight loss (Schifter & Ajzen, 1985) and dietary health behaviours (Ajzen & Timko, 1986), although not in all applications (Fishbein & Stasson, 1990). In a study of biscuit and bread consumption (Sparks et al 1992), intentions to consume wholemeal bread were not influenced by perceived control but intentions to consume biscuits were.…”
Section: The Theory Of Planned Behaviourmentioning
confidence: 99%
“…Drawing on previous motivation (e.g., Fishbein & Stasson, 1990;Hurtz & Williams, 2009;Singer, 1991;Tubbs & Ekeberg, 1991) and leadership theories (e.g., Ashforth, 2001;Charan et al, 2001;Ibarra et al, 2010;Lord & Hall, 2005), we propose that self-exemplar role comparisons are mainly performed with the identity verification purpose of assessing personal adjustment with the leadership role in terms of skills and behaviors (i.e., manifest self-concept dimensions), and they serve to gain confidence in feeling capable of succeeding in the leadership role (i.e., the "I can" component of motivation). In contrast, self-prototypical role comparisons are used with the identity verification purpose of assessing the individual match to the leadership role in terms of values, meanings or ideologies (i.e., deep self-concept dimensions), and they serve to evaluate the extent to which leadership activities are attractive, self-relevant and fuel authentic feelings (i.e., the "I like" component of motivation).…”
Section: Types Of Self-to-role Comparisons and The Motivation To Leadmentioning
confidence: 99%